Behavior of Deep Beams with Different Proportions of Recycled Plastic Type HDPE Instead of Coarse Aggregate - Abawi, Ahmed M.; Salih, Oday Asal (Civil Engineering Journal, 2025)
One of the most appealing strategies in the ongoing effort to lessen humans' impact on the environment is using waste plastic as coarse particles in concrete. This innovative approach addresses the pressing issue of mounting plastic waste and aims to diminish the adverse effects of traditional building materials, such as natural aggregates, on the environment. Plastic waste as coarse aggregates exemplifies a professional dedication to creating a resilient infrastructure that mitigates environmental harm and contributes to a greener future for future generations. Eight deep beams were cast with sustainable concrete that was made from two mixtures: one in normal strength (C30) and the other in high-strength concrete (HSC) (1% Hyperplast PC200 of cement) that included HDPE plastic, which was taken from fruit boxes that had been crushed and used in 10, 20, and 30 percentage volumetric proportions as a substitute for coarse aggregate. The two still intact have no HDPE replacement and serve as each deep beam's reference deep beam. Shear failure and ductility in the second group were slightly lower than 2% compared to the reference beam for B30. It can be argued that while the replacement has positive environmental impacts, the 23.5% loss in strength is unwanted, while the 2% decline in ductility is acceptable. While maintaining a competent structural flexural behavior, the first group demonstrated an increase in shear failure by the replacement rate (20%, 30%), and the 10% replacement rate dropped by a tiny percentage (1.25%) in comparison to the reference specimen.